THE VOICE OF THE CHILD: AN ANALYSIS OF THE CHILD PROTECTION SYSTEM IN LITHUANIAN FAMILY SOCIAL WORK - Eidukevičiūtė, Julija; Motiečienė, Roberta; Naujanienė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This paper explains the current practices of the child welfare system in the context of Lithuania. In Europe, research on child welfare has a long history; however, the child welfare situation in Lithuania has not been systematically studied, nor has it been provided with the research-based knowledge necessary for the development of the system. Based on qualitative research results, the paper sheds light on how the voice of the child is heard in Lithuanian child and family social work practice. The research participants in the present study were children and family social workers. The research results indicate that adult-centered family social work practices are dominant and the voice of the child is misleading in the intervention process.